Evaluation of the axonics modulation technologies sacral neuromodulation system for the treatment of urinary and fecal dysfunction. (2nd January 2017) - Cohn, Joshua A.; Kowalik, Casey G.; Kaufman, Melissa R.; Reynolds, W. Stuart; Milam, Douglas F.; Dmochowski, Roger R.
ABSTRACT: Introduction : Sacral neuromodulation (SNM) remains one of the few effective treatments for refractory bladder and bowel dysfunction. However, SNM is associated with frequent need for surgical intervention, in many cases because of a failed battery. A rechargeable SNM system, with a manufacturer-reported battery life of 15 years or more, has entered post-market clinical testing in Europe but has not yet been approved for clinical testing in the United States. Areas covered : We review existing neuromodulation technologies for the treatment of lower urinary tract and bowel dysfunction and explore the limitations of available technology. In addition, we discuss implantation technique and device specifications and programming of the rechargeable SNM system in detail. Lastly, we present existing evidence for the use of SNM in bladder and bowel dysfunction and evaluate the anticipated trajectory of neuromodulation technologies over the next five years. Expert commentary : A rechargeable system for SNM is a welcome technological advance. However surgical revision not related to battery changes is not uncommon. Therefore, while a rechargeable system would be expected to reduce costs, it will not eliminate the ongoing maintenance associated with neuromodulation. No matter the apparent benefits, all new technologies require extensive post-market monitoring to ensure safety and efficacy.